2019
DOI: 10.1109/access.2019.2920242
|View full text |Cite
|
Sign up to set email alerts
|

Validation of TAM Model on Social Media Use for Collaborative Learning to Enhance Collaborative Authoring

Abstract: Increased impact of technology leads numerous studies to conduct research on the effect of social media on performance. Very limited of such studies have tried to observe and record the use of social media for collaborative learning as a way to improve collaborative authoring. This paper tries to the validation of the technology acceptance model (TAM) on social media use for collaborative learning to enhance collaborative authoring among research students. To achieve the study objective, this paper employed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 53 publications
4
89
0
4
Order By: Relevance
“…Thus, "this research defines educational use at a degree where a student's beliefs educational use with peers would enrich their teaching and learning". These results are consistent with [12,25,30,27,31,32], who argued that educational use with peers was useful on educational use. See Table 4.…”
Section: A Descriptive and Examination Of Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, "this research defines educational use at a degree where a student's beliefs educational use with peers would enrich their teaching and learning". These results are consistent with [12,25,30,27,31,32], who argued that educational use with peers was useful on educational use. See Table 4.…”
Section: A Descriptive and Examination Of Factorssupporting
confidence: 92%
“…Thus, "this research defines attitude toward use at a degree where a student's beliefs attitude toward use social media would enrich their teaching and learning". These results are consistent with [30,39,40,41,42,43], who argued that attitude toward use social media was useful on teaching and learning. See Table 7.…”
Section: A Descriptive and Examination Of Factorssupporting
confidence: 89%
“…Several studies have reported that (SNAs) have an important role in enhancing the students' engagement as well as in their achievements [55]. Learners' performance impact as sustainability in higher education has been found to be significantly improved by the use of (SNAs) in academics [29,56]. It also has a positive influence on skill development [12] and improving cognitive skills [30,57].…”
Section: J Performance Impact As Sustainability In Higher Educationmentioning
confidence: 99%
“…Educational quality can be defined as the extent to which the IS system has succeeded in having a definite outline precisely marked to provide learners with a conducive learning environment in terms of collaborative learning [41]. It can be seen that the ideals of quality online education as mentioned above are well in line with the fundament truth or proposition that serves as the foundation for a system of belief or behaviour or for the educational quality of reasoning.…”
Section: 4educational Qualitymentioning
confidence: 99%